Evaluasi Pengembangan Green Skills dalam Pendidikan Kejuruan di Indonesia: Tinjauan Literatur - Irba' Rizka Putri; Waras Dwi Yoga; Tiara Kusuma Dewi; Danar Susilo Wijayanto; Sri Sumarni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
The transition to a green economy requires vocational education to produce graduates who possess not only technical skills but also sustainability competencies, or ‘green skills’. This study aims to evaluate the development of green skills in vocational education in Indonesia, identify barriers to their implementation, and analyze the effectiveness of green skills learning on students’ competencies. The research employed a literature review using a narrative-integrative approach, involving thematic analysis and synthesis of academic articles, policy documents, and other relevant literature. The findings indicate that the implementation of green skills in vocational education in Indonesia has begun to develop, but has not yet been systematically integrated into the curriculum, teaching, and assessment. The main obstacles include teachers’ limited understanding, the lack of explicit integration of green skills into the curriculum, the lack of contextual relevance in teaching strategies, an evaluation system that is not yet authentic, and a weak link to the needs of the green industry. Furthermore, project-based learning, problem-based learning, Project Citizen, and real-world practical experience have demonstrated their potential to effectively enhance pupils’ technical, problem-solving, and communication skills, as well as their environmental responsibility and employability. The findings of this study confirm that the development of green skills requires policy support, capacity building for teachers, innovation in teaching and learning, and closer collaboration between vocational education and the industry to support the transition towards sustainable development.